Does saline water consumption affect feeding and fuel deposition rate of a staging, long‐distance migrating passerine?. (17th December 2015) - Efrat, Ron; Shani, Gavriella; Gutman, Roee; Sapir, Nir
Abstract : To accomplish their enduring journeys, migrating birds accumulate fuel consisting mainly of lipids in stopover sites located throughout their migration routes. Fuel deposition rate (FDR) is considered a key parameter determining the speed of migration and thereby bird fitness, and recent studies have demonstrated the positive effects of fresh water consumption on the FDR of migrating blackcaps Sylvia atricapilla . Sewage water reservoirs, characterized by higher water salinity than fresh water, were extensively built in different parts of the world and are used by birds during their travel, but their effects on wildlife and specifically on migrating birds have been largely overlooked thus far. We experimentally examined the effects of water salinity on blackcap FDR during migration. We captured birds in an autumn stopover site, transported them to the laboratory and provided them with fruits, mealworms and water of different salinity levels (0.3, 4.5 and 9‰ NaCl) for several days. We examined the effects of water salinity on the blackcaps' diet, water consumption and FDR and found that FDR was mainly affected by fruit consumption rate and not by the water salinity levels. Water salinity nevertheless caused elevated water consumption as the birds consumed almost 3 times more saline water than fresh water per consumed fruit mass. Our work is the first to explore the consequences of saline water consumption on migrating passerines, specifically suggesting that anthropogenic alterations of habitats by sewage water treatment facilities may modulate bird nutrition and diet.